Nonviolent Buddhist Peace Work: Textual Support for Nonviolent Peace Work in Early Buddhism - Strickler, Weston Elliot (The Journal of International Association of Buddhist Universities (JIABU), 2018)
In this paper, I will explore if there is evidence for the support of nonviolent peace work in the early Buddhist tradition. First, I will describe the social science’s definitions for the three modalities of peace work, then I will highlight current peace organizations and prominent peace workers in the modern Buddhist tradition. Lastly, I will examine the first four Nikāyas and the Vinaya of the Pāli Buddhist canon to see if the idea of nonviolent peace work, as defined within Peace and Conflict Studies, has textual support.